Field and Laboratory Studies of the Susceptibility of the Green Treefrog (Hyla cinerea) to Batrachochytrium dendrobatidis Infection - Brannelly, Laura A.; Chatfield, Matthew W. H.; Richards-Zawacki, Corinne L. (PLOS ONE, 2012)
Amphibians worldwide are experiencing devastating declines, some of which are due to the amphibian chytrid fungus (Batrachochytrium dendrobatidis, Bd). Populations in the southeastern United States, however, have not been noticeably affected by the pathogen. The green treefrog (Hyla cinerea) is abundant and widespread in the southeastern United States, but has not been documented to harbor Bd infection. This study examined the susceptibility of H. cinerea to two strains of Bd in the lab and the prevalence of infection in wild populations of this species in southeastern Louisiana. Although we were able to infect H. cinerea with Bd in the lab, we did not observe any clinical signs of chytridiomycosis. Furthermore, infection by Bd does not appear to negatively affect body condition or growth rate of post-metamorphic individuals. We found no evidence of infection in surveys of wild H. cinerea. Our results suggest that H. cinerea is not susceptible to chytridiomycosis post-metamorphosis and probably is not an important carrier of the fungal pathogen Bd in the southeastern United States, although susceptibility at the larval stage remains unknown.